Effect of the Hot Streak on the Overall Cooling Performance of a Coated Rotor Blade - Li Shi; Yuanfeng Lu; Hanze Huang (Energies, 2022)
The influence of the HS (hot streak) and unsteady wake on the overall cooling performance of a rotor blade was studied in this paper. The results show that: (1) Both the magnitude and temperature of the HS gradually drops down as it passes downstream of the vane passage. (2) Within one stator period, the highest cooling performance of the blade can be observed at the initial time points, when the LE (leading edge) of the blade turns towards the trailing edge of the vane. (3) The lowest cooling performance of the blade can be observed at the time point 0.5 T, when the LE of the blade turns towards the center of the vane passage. (4) Surface temperatures in areas with unfavorable local heat flow are usually higher than the temperature of the coolant. The additional TBCs may exert adverse effects on heat dissipation from the substrate metal to the mainstream, which has a negative effect on the improvement of the overall cooling effectiveness of the coated blade. (5) Within a stator period, a relatively higher overall cooling effectiveness increment due to the coating can be observed at the relative location with lower cooling performance. Consequently, the additional TBCs are beneficial for decreasing the surface temperature difference and thus controlling the thermal stress under the HS inlet condition.